2014
DOI: 10.1007/s00345-014-1314-5
|View full text |Cite
|
Sign up to set email alerts
|

The role of MRI-targeted and confirmatory biopsies for cancer upstaging at selection in patients considered for active surveillance for clinically low-risk prostate cancer

Abstract: MRI-TB and confirmatory SB upstaged 59 % of cases, improving the selection of patients considered for AS at the first series of SB. Variation in histologic grade assignation between centres and better cancer sampling may explain this high upstaging rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
1
5

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 18 publications
2
26
1
5
Order By: Relevance
“…The upgraded proportion due to the TRUS‐guided biopsies was 20% (95% CI 16–25%; Table ), which is slightly higher than the ~15% in published reports at confirmatory assessment . Part of the upgrading could be influenced by the unblinded study design in two reports , favouring the TRUS‐guided biopsies. However, one study explicitly reported excluding areas that had been previously sampled with the MRI‐targeted biopsy approach favour the MRI and targeted‐biopsies approach .…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…The upgraded proportion due to the TRUS‐guided biopsies was 20% (95% CI 16–25%; Table ), which is slightly higher than the ~15% in published reports at confirmatory assessment . Part of the upgrading could be influenced by the unblinded study design in two reports , favouring the TRUS‐guided biopsies. However, one study explicitly reported excluding areas that had been previously sampled with the MRI‐targeted biopsy approach favour the MRI and targeted‐biopsies approach .…”
Section: Discussionmentioning
confidence: 80%
“…Studies on MRI and AS were excluded if MRI had previously been used (initial biopsies or previous negative biopsies) , if data on negative prostate MRI was excluded , if Gleason score 3 + 4 at initial TRUS biopsy was also included in the AS cohort , if sampled lesions with suspicion score of ‘2’ on MRI could not be excluded from the results , when MRI suspicion scores (Likert or PI‐RADS) were dichotomised as positive to a score ≥4 instead of a score ≥3 , if template biopsies (>20 cores) was used as the reference test , if data extraction to 2 × 2 contingency tables was not possible , if a transperineal biopsy approach , or unclear definition of index test was used . We excluded double publications .…”
Section: Methodsmentioning
confidence: 99%
“…Marliere et al and Hu et al separately reported their experience with the mpMRI as a predictor of CBx using a fusion‐guided biopsy and different available software. Both authors included a 5‐point scale to grade the probability of high‐risk disease on mpMRI, but only Hu et al followed START guidelines .…”
Section: Discussionmentioning
confidence: 99%
“…Henderson et al [24] focused on MRI in AS and concluded that MRI is a useful marker when selecting patients for AS and may help in predicting whether patients should receive close monitoring or whether immediate treatment should be given. We think that MRI is very useful for selecting patients for AS and for detecting cancer upgrading [25]. Especially, lesions in the apex or anterior of the prostate are difficult to find.…”
Section: Discussionmentioning
confidence: 99%